All-American murder : the rise and fall of Aaron Hernandez, the superstar whose life ended on murderers' row - Patterson, James, 1947-; Abramovich, Alex, 1972-; Harvkey, Mike (New York : Grand Central Publishing, 2018)
"He was a college All-American who became the youngest player in the NFL and later a Super Bowl veteran. He was a star tight end on the league-dominant New England Patriots, who extended his contract for a record $40 million. Aaron Hernandez's every move as a professional athlete played out in the headlines, yet he led a secret life -- one that ended in a maximum security prison. What drove him to go so wrong, so fast?"--
Keywords: Hernandez, Aaron, -- 1989-2017.; Hernandez, Aaron, -- 1989-2017 -- Trials, litigation, etc; New England Patriots (Football team); Murder -- Massachusetts -- Case studies; Trials (Murder) -- Massachusetts -- Case studies; Football players -- United States -- Biography; True crime stories; Biographies; Biographies; Biography; Case studies; Trials, litigation, etc; True crime stories; Biographies